Structural and biochemical differences between non-catalytic and catalytic antibodies - Taizo Uda; Ryuichi Kato; Yasuteru Shigeta; Shun Hirota; Jun Kobayashi; Hisashi Yoshida; Masato Tsuyuguchi; Kowit Hengphasatporn; Moe Tsujita; Hiroaki Taguchi; Emi Hifumi (mAbs)
A conventional antibody can be converted into its catalytic counterparts by deleting Pro95 in the CDR-3 of human and mice antibody light chains, as previously reported. T99wt is a naturally occurring human antibody light chain that we transformed into its catalytic antibody using Pro95 deletion. In peptidase activity tests, T99wt exhibited a low catalytic activity against a synthetic peptide Arg-pNA and hardly cleaved amyloid-β peptide. In contrast, the engineered variant (T99-Pro95(-)) demonstrated significant catalytic activity, effectively cleaving both Arg-pNA substrate and amyloid-β peptides. In this study, the structural basis for the acquisition of enzymatic function through Pro95 deletion in the CDR-3 region of the light chain was elucidated using X-ray crystallography and molecular dynamics (MD) simulations. X-ray crystallography revealed that Pro95 deletion substantially reduces the distance between Asp1 and His93—key residues for catalytic activity – from 9.56 Å in T99wt to 3.84 Å in T99-Pro95(-). The observed decrease in distance indicates a strong interaction between Asp1(Oδ1) and His93(Nε2), contributing to the formation of an active site in T99-Pro95(−). MD simulations revealed that the entire structure exhibits slight fluctuations and adopts various configurations upon the removal of Pro95. In particular, when His residues in the catalytic region are fully deprotonated, Asp1, His93, and Ser27a transiently come into close proximity, enabling the formation of a functional catalytic triad. Catalytic antibodies can be made starting from just the amino acid sequence of a desired mAb, which may be available in databases such as OAS or IMGT. Therefore, our finding represents a significant technological advancement.